Spirodesmos milanai n. isp.: A shallow-water spiral trace fossil from the Cambrian of the Eastern Cordillera, northwest Argentina - Aceñolaza, Guillermo Federico (2005)
A new ichnofossiliferous locality in Salta Province (northwest Argentina) contains an association with numerous irregular spiral traces assigned to Spirodesmos milanai n. isp., in mature sandstones and quartzites with rippled bedding surfaces, rare wavy lamination and cross-bedded stratification. This record of early spiral behavior is interpreted as a primitive grazing method formed on muddy laminae above sand layers, and is related to a feeding strategy of an annelid-type of organism. Associated traces are Cruziana cf. semiplicata, Diplocraterion isp., Monocraterion isp., Rusophycus isp., Skolithos linearis Haldeman and Skolithos magnus Howell. The ichnoassemblage is similar to a shallow-water ichnoassociation from the Permian Ecca Group of South Africa (Mason et al., 1983. Copyright © Taylor & Francis Inc.